Formação de complexos supramoleculares entre estruturas carreadoras e moléculas bioativas. - Hudson, Eliara Acipreste (2021)
Bioactive compounds have the property of modulating several metabolic processes, but their bioactivity is dependent on their stability and bioavailability. Thus, the formation of supramolecular complexes between bioactive molecules and natural macromolecules, such as proteins and cyclodextrins, is an interesting strategy for the incorporation of bioactive substances in different matrices to maintain their bioactivity. For this, it is essential to characterize the interactions that promote and sustain the formation ofthese complexes, as well as to know their formation and dissociation kinetics. This work was divided into three scientific articles and aimed to characterize the intermolecular interactions of the following systems: micelle of casein-curcumin (MC-CUR), P-casein-quercetin (B-cas-Qet), P-cyclodextrinresveratrol/structural analog (B-CD-RES and B-CD-RESAnl).In the first article, the formation of the MC-CURcomplex, the carrying capacity of MC and its thermal protection for CUR at a pH of 6.6 was studied. It has been shown that an MC can carry around 18,000 molecules of CUR. The thermodynamic parameters indicated an enthalpically driven complex formation process (AHº = —64.63 kJ-mol! and TASº ranging from —42.45 to —44.46 kJ-mol"!). Theincrease in temperature reduced the rate of formation of the MC-CUR complex and increased its rate of dissociation. The activation energy for the formation of activated MC-CUR complexes was negative for the association of free MC and CUR molecules (-62.8 kJ-mol!) and positive for the dissociation of thermodynamically stable complexes (1.80 kJ:mol). MC protected CUR against its thermal degradation. In the second article, it was demonstrated that B-cas and Qct form thermodynamically stable supramolecular complexes in a process driven by an increase in the entropy ofthe system (AHº= 25.86 and TASº= 53.49 kJ-mol! at 25 ºC),via formation of an activated complex driven by an entropic reduction (TAS*a= -15.31 kJ-mol! and TAS*a= - 68.80 kJ-mol! at 25 ºC) and an enthalpic increase (AH*(a = 30.87 and AH*(q = 5.0 kJ-mol! at 25 “C). The addition of both salts, KCl or KSCN,increased the stability of the complex by decreasing the values of the kinetic and thermodynamic enthalpies. In the third article, the interaction kinetics between modified B-CD (B-CD-NH;,) and RES, as well as its structural analog (RESAnl) was determined. The inclusion of RESAnl, as well as its dissociation from B-CD-NH,, were faster than the same processes that occurred with RES as a guest molecule (kBTCD=NH2/RESANI340,101 Mis, KBTCD=NHaIRES4 97410) Mig; kbP“CD-NH2/RESANI039 gl, kBCD=NHa/RES-0,30 sl, at 25 ºC). The structural differences between the polyphenols (RES and RESAnl) affected the energetic parameters of formation of the activated complex more via the association of free molecules than via dissociation from the E$TCD-NHa/RES =1481 k-mol'! EBTCD- 2/RESAn1 thermodynamically stable complexes (Eqc+a acta 15.01 to 82.35 kJmol!), (EÉZO-NH/RES 5.19 kJmol! and EÉSONHRESA 6,29 kJ-mol!). These differences are mainly due to the desolvation process of the interacting molecules. It is concluded that the thermodynamic and kinetic parameters obtained for each of the studied systems, as well as the results of the complementary analyzes, are important foundations for optimizing the application of these bioactive molecular complexes in different food or pharmaceutical systems. Keywords: Bioactive compounds. Supramolecular complexes. Caseins. B-cyclodextrin. Curcumin. Quercetin. Resveratrol. Thermodynamics. Kinetics.